Nursing Students' Perceptions of Post COVID-19's Role in Nursing Professionals - Kang, Se-Won (Advances in Social Sciences Research Journal, 2020)
This study examined the perception of nursing students about the role of the nursing professionals on post COVID-19. The survey was conducted online with 50 nursing students. Results of this study indicated that the scores for the importance of the nursing profession on post COVID-19 were the highest in the areas of infection control, emergency, and critical care. In addition, the areas of the nursing profession that needed to expand their role were identified as infection control, emergency, and public health, respectively. It is necessary to prepare for each nursing specialty to provide services as health care providers in the post COVID-19 era.